Ethnographic Commentary (Soviet Ethnography) Magazine Review of Uzbek People's Ethnoculture - Jasurbek Mamatov (Genius Journals, 2022)
This article analyzes the history of the journal «Ethnographic Review (Soviet Ethnography)», published in Russia since 1889, its long history, the editors of the magazine, the articles on the material and spirituality of the Uzbek people. The main focus of the article is to study the local features of the centuries-old ethnoculture of the Uzbek people, presented in the pages of magazines by Russian, Soviet and local researchers.
Keywords: Ethnography; ethnology; Ethnographic commentary; customs